Potensi Aktivitas Antidiabetes Berbagai Jenis dan Varian Tanaman Mangga (Mangifera spp.) - Agnes Monica Murisla; Zulpakor Oktoba; Femmy Andrifianie; Ramadhan Triyandi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Diabetes mellitus is a chronic disease with a significantly increasing global prevalence, especially in developing countries. Current treatments use synthetic antidiabetic drugs that are generally expensive and have various side effects. This study aims to examine the potential of mango plants (Mangifera spp.) as antidiabetic agents through a systematic literature review. Literature searches were conducted through the electronic databases PubMed and Google Scholar using the keywords